Immunological Aspects of AXL/GAS‐6 in the Context of Human Liver Regeneration. Issue 3 (24th December 2021) - Ortmayr, Gregor; Brunnthaler, Laura; Pereyra, David; Huber, Heidemarie; Santol, Jonas; Rumpf, Benedikt; Najarnia, Sina; Smoot, Rory; Ammon, Daphni; Sorz, Thomas; Fritsch, Fabian; Schodl, Michael; et al.
Abstract : AXL and its corresponding ligand growth arrest–specific 6 (GAS‐6) are critically involved in hepatic immunomodulation and regenerative processes. Pleiotropic inhibitory effects on innate inflammatory responses might essentially involve the shift of macrophage phenotype from a pro‐inflammatory M1 to an anti‐inflammatory M2. We aimed to assess the relevance of the AXL/GAS‐6‐pathway in human liver regeneration and, consequently, its association with clinical outcome after hepatic resection. Soluble AXL (sAXL) and GAS‐6 levels were analyzed at preoperative and postoperative stages in 154 patients undergoing partial hepatectomy and correlated with clinical outcome. Perioperative dynamics of interleukin (IL)‐6, soluble tyrosine‐protein kinase MER (sMerTK), soluble CD163 (sCD163), and cytokeratin (CK) 18 were assessed to reflect pathophysiological processes. Preoperatively elevated sAXL and GAS‐6 levels predicted postoperative liver dysfunction (area under the curve = 0.721 and 0.722; P < 0.005) and worse clinical outcome. These patients failed to respond with an immediate increase of sAXL and GAS‐6 upon induction of liver regeneration. Abolished AXL pathway response resulted in a restricted increase of sCD163, suggesting a disrupted phenotypical switch to regeneratory M2 macrophages. No association with sMerTK was observed. Concomitantly, a distinct association of IL‐6 levels with an absent increase of AXL/GAS‐6 signaling indicated pronounced postoperative inflammation. This was further supported by increased intrahepatic secondary necrosis as reflected by CK18M65. sAXL and GAS‐6 represent not only potent and easily accessible preoperative biomarkers for the postoperative outcome but also AXL/GAS‐6 signaling might be of critical relevance in human liver regeneration. Refractory AXL/GAS‐6 signaling, due to chronic overactivation/stimulation in the context of underlying liver disease, appears to abolish their immediate release following induction of liver regeneration, causing overwhelming immune activation, presumably via intrahepatic immune regulation. Abstract : image